Application of fluorouracil and adjustable suture on surgery treatment for acute attack of primary angle-closure glaucoma in middle-aged patients - Ying-Hui Ma (Guoji Yanke Zazhi, 2020)
AIM: To investigate the effect of combined application of fluorouracil and adjustable suture in trabeculectomy for acute attack of primary angle-closure glaucoma in middle-aged patients. METHODS: This was a prospective study. 60 patients(60 eyes)with primary angle-closure glaucoma in middle-aged patients were selected in our hospital from October 2016 to March 2019. Patients were randomly divided into suture group, 5-FU group and combined group, with 20 cases(20 eyes)in each group. Followed up for 6mo postoperatively, the patient's vision, visual field, intraocular pressure, adjuvant therapy and quality of life were observed. RESULTS:The best corrected visual acuity among the three groups in the first week after operation was higher than that before surgery(P<0.05). The intraocular pressure of the three groups at one week, one month and six months after operation were lower than that before operation(all P<0.05). The intraocular pressure in the combined group were significantly lower than that in the suture group and the 5-FU group at 1mo and 6mo after operation(all P<0.05). The number of eyes with anti-glaucoma drugs(2 eyes)and the number of anti-glaucoma drugs(0.20±0.016)in the combined group after operation were significantly lower than those in the suture group(11 eyes, 0.90±0.068)and the 5-FU group(12 eyes, 0.95±0.045)(all P<0.05). There was no significant differences in preoperative CLVQOL scores among the three groups(P>0.05). The CLVQOL scores of the combined group(110.60±2.44)was higher than that of the suture group(101.50±2.61)and the FU group(98.55±2.50)at 6mo after operation(P<0.05). The increase of CLVQOL scores(34.50±4.36)in the combined group before and after operation was significantly higher than that in the suture group(25.80±3.59)and the FU group(23.05±5.44)(P<0.05). CONCLUSION: Combined use of 5-FU and adjustable suture in trabeculectomy for the treatment of acute attack of middle-aged primary acute angle-closure glaucoma patients is safe and effective, which can improve the quality of life.